Is an exercise-based injury-prevention program effective in team handball players? a systematic review and meta-analysis - Naderi, A.; Shaabani, F.; Keikha, M.; Degens, H. (Journal of Athletic Training, 2024)
Objective: To assess the effectiveness of exercise-based injury-prevention programs in preventing sports injuries in team handball players. Data Sources: Scopus, PubMed, Web of Science, SPORTDiscus, and CINAHL from inception until April 2023. Study Selection: Studies were included if they were randomized controlled trials or prospective cohort studies, contained a population of competitive team handball players, included an intervention designed specifically to prevent or reduce the risk of team handball injuries, and reported injury incidence rates specific to team handball players. Two researchers independently evaluated studies for inclusion and assessed their methodological quality. Data Extraction: Study design, intervention details, participant characteristics, and the number of injuries in each group were extracted from each study by 2 independent researchers. The outcome of interest was the incidence rate of injury. Injury data were classified into 5 groups: shoulder injuries, lower extremity injuries, knee injuries, anterior cruciate ligament injuries, and ankle injuries. Extracted data were analyzed using a random-effects model to compute the overall effect estimates of injury-prevention programs in reducing the risk of injuries. Odds ratios (ORs) with 95% CIs were calculated based on the number of injuries in each group. Data Synthesis: Meta-analyses were conducted independently for each injury classification. Results indicated that prevention programs reduced the risk of shoulder injuries (OR = 0.60; 95% CI = 0.42, 0.85; P = .004), lower extremity injuries (OR = 0.59; 95% CI = 0.37, 0.95; P = .03), knee injuries (OR = 0.53; 95% CI = 0.35, 0.78; P = .002), anterior cruciate ligament injuries (OR = 0.66; 95% CI = 0.45, 0.96; P = .03), and ankle injuries (OR = 0.57; 95% CI = 0.40, 0.81; P = .002) in team handball players. Conclusions: In team handball players, injury-prevention programs appear to effectively reduce the risk of shoulder, lower extremity, knee, ankle, and anterior cruciate ligament injuries.